(untitled) (Research, Society and Development, 2022)
The United Nations Organization for Education, Science and Culture (UNESCO, 2011) stated that Information and Communication Technologies (ICT`s), can improve the teaching-learning process. For this it is necessary to have a reform of conventional teaching systems and the increase in the quality of learning, through training focused on developing the skills required by the Information Society (UNESCO, 2011). However, due to the pandemic, this reform was carried out in an untimely manner, which led the educational system to face a transcendental moment, since a large part of the universities were closed, and face-to-face education changed to non-face-to-face education. According to a UNESCO report in 2020, some 185 countries suspended classes completely, which implies more than 1,500 million students affected, is where the questions arise: are teachers prepared for this change? non-face-to-face education? This research, through a systematic review, aims to provide an answer to these questions, specifically in the area of ​​social and health sciences, in speech language professionals who teach in the non-face-to-face online educational modality in the context of the COVID-19 pandemic. Based on this review, it is possible to point out that non-face-to-face online education offers a large number of opportunities, but, as well as offering opportunities, it also presents significant challenges to maintain educational quality and relevance. To take advantage of the advantages offered by the new modalities, continuous improvement in the practice of distance education is necessary, seeking the best strategies for teaching and the development of students who are inclined to receive their academic training under this modality.